2012
DOI: 10.1021/jp306447n
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Electrophoretically Deposited Films on Electrode Strips

Abstract: Studies of the kinetics of electrophoretic deposition (EPD) processes have generally focused on electrode geometries that yield analytical solutions, such as infinite parallel planes and concentric cylinders. In this article, we construct a finite element model for EPD of material onto a planar strip electrode which shows excellent qualitative agreement to experimental results in a similar system. Notably, we demonstrate that the presence of the edges of the electrode lead to a singularity in the electric fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…The cross sectional profi le of a representative deposited strip with the 1.25 mm mask is presented in Figure 2 d. In this case, the deposit is approximately 9 µm thick at the center and 14 µm thick at the edges. This is a characteristic of deposits on electrode strips as observed by Pascall et al, [ 35 ] and, as they showed, is a result of a singularity in the electric fi eld that results from a discontinuity in the electric boundary conditions at the edge of the electrode, or in this case, at the boundary between the illuminated and dark areas of the photoconductive electrode. This is a characteristic of deposits on electrode strips as observed by Pascall et al, [ 35 ] and, as they showed, is a result of a singularity in the electric fi eld that results from a discontinuity in the electric boundary conditions at the edge of the electrode, or in this case, at the boundary between the illuminated and dark areas of the photoconductive electrode.…”
Section: Communicationmentioning
confidence: 69%
See 1 more Smart Citation
“…The cross sectional profi le of a representative deposited strip with the 1.25 mm mask is presented in Figure 2 d. In this case, the deposit is approximately 9 µm thick at the center and 14 µm thick at the edges. This is a characteristic of deposits on electrode strips as observed by Pascall et al, [ 35 ] and, as they showed, is a result of a singularity in the electric fi eld that results from a discontinuity in the electric boundary conditions at the edge of the electrode, or in this case, at the boundary between the illuminated and dark areas of the photoconductive electrode. This is a characteristic of deposits on electrode strips as observed by Pascall et al, [ 35 ] and, as they showed, is a result of a singularity in the electric fi eld that results from a discontinuity in the electric boundary conditions at the edge of the electrode, or in this case, at the boundary between the illuminated and dark areas of the photoconductive electrode.…”
Section: Communicationmentioning
confidence: 69%
“…The origin of increased thickness of the edges is described by Pascall et al[ 35 ] b) Feature size reproduction of the technique with mask feature widths ranging from 0.25 to 5 mm.…”
mentioning
confidence: 99%
“…It is worth noting that, even though the observed microstructures are representative for the layers obtained from the different suspensions under the conditions here defined, the modification of the deposition conditions lead to a different morphology of the as-deposited samples and to a different sintering behavior. For instance, the increase in the deposition time for a defined suspension, which gives place to thicker deposits with a less pronounced U-shape according to Pascall et al, 25 results in sintered films with diverse microstructures. Further focused studies are in progress in order to investigate the effect of the film thickness on the microstructure of PZT-Nb thick films.…”
Section: Influence Of the Co-solvents In The Properties Of The Suspenmentioning
confidence: 99%
“…[3,4] Recently, there has been a focus on manufacturing energetic thin films for material synthesis applications [5][6][7][8][9] and creating tailored shapes for customized power generation applications. [10] Processing energetic materials for tailored shapes can be achieved through quiescent sol-gel synthesis, [11] vapor/spray deposition, [12,13] blade casting, [14,15] or through additive manufacturing techniques. [16,17] All of these processes require combining energetic materials with a polymer binder and carrier fluid that acts to disperse the reactant matrix into a polydisperse colloidal slurry.…”
Section: Introductionmentioning
confidence: 99%